2020
DOI: 10.14336/ad.2019.0510
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Ameliorates Cardiac Dysfunction via Balancing Mitochondrial Dynamics and Inhibiting Apoptosis in Type 2 Diabetic Mice

Abstract: The ketogenic diet (KD) has been widely used in clinical studies and shown to hace an anti-diabetic effect, but the underlying mechanisms have not been fully elaborated. Our aim was to investigate the effects and the underling mechanisms of the KD on cardiac function in db/db mice. In the present study, db/db mice were subjected to a normal diet (ND) or KD. Fasting blood glucose, cardiac function and morphology, mitochondrial dynamics, oxidative stress, and apoptosis were measured 8 weeks post KD treatment. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
5
41
0
Order By: Relevance
“…Our results were supported by a recent population-based study, which concluded a deleterious result on the coronary artery conferred by low-carbohydrate diet that is similar to KD [3]. However, the findings of the current study supporting the unflavored role of KD in diabetes is sharply in contrast to the previous study, showing beneficial effects of KD in cardiomyocyte survival and interstitial fibrosis [4]. The differences of animal characteristics could be the most plausible explanation of this discrepancy.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our results were supported by a recent population-based study, which concluded a deleterious result on the coronary artery conferred by low-carbohydrate diet that is similar to KD [3]. However, the findings of the current study supporting the unflavored role of KD in diabetes is sharply in contrast to the previous study, showing beneficial effects of KD in cardiomyocyte survival and interstitial fibrosis [4]. The differences of animal characteristics could be the most plausible explanation of this discrepancy.…”
Section: Discussionsupporting
confidence: 76%
“…The serum insulin levels also supported the distinct characteristics of the animal used in our and the previous study. Levels of serum insulin were dramatically decreased in db/db mice in the study by Guo et al [4], while it is well acknowledged that hyperinsulin is one of the basic characteristics of db/db mice as found in the current and many other studies [19,29,30], which is the basic pathophysiological alterations of T2DM. Therefore, the animal used in the current study, which reflects the canonical T2DM leading to cardiac remodeling, is distinct from the previous one and this could cause different responses to KD treatment.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Additionally, there is substantial literature describing improvement in rodent cardiomyopathy models using "non-ketogenic" high fat or PUFA-enriched diets in the absence of obesity 58 . Interestingly, ketogenic diet was recently shown to improve cardiac remodeling in the obese db/db mouse model 59 , potentially due to the improved insulin sensitivity with significant carbohydrate restriction. However, in the setting of obesity and insulin resistance, increased dietary fat may add to cardiac lipid accumulation or "lipotoxicity" 60 .…”
Section: Discussionmentioning
confidence: 99%